Results Of The Conducted Multifactorial Experiments To Substantiate The Parameters Of The Rotary Ripper Machine For Processing Ridges - Igamberdiev, Anvarjon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
The article presents the results of multifactorial experimental studies to substantiate the optimal values of the number, height of the slats and the angle of installation to the direction of movement of the conical rollers of the rotary ripper developed by the machine for processing ridges in early spring.